Technical training of young ski jumpers using simulation - Zakharov, G. G.; Novikova, N. B.; Belyova, A. N.; Kotelevskaya, N. B. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the compliance of simulation exercises of young ski jumpers aged 12-14 with modern technical requirements.